The Impact of Tutor Quality, Leadership Practices and Infrastructure on the Academic Work of Teacher-Trainees in Selected Colleges of Education in the Ashanti Region of Ghana (International Journal of Scientific Research and Management (IJSRM), 2018)
The study aimed at investigating the extent to which Tutor quality, Leadership practices, Infrastructure, impact on academic work of Teacher-trainees. A survey research design was used for the study because it involved a study of relatively large population who were purposively and randomly selected. A sample size of 322 out of the population of 1850 from Offinso, Akrokerri and Wesley Colleges of Education comprising 226 males and 114 females were used for the study. A questionnaire and an interview guide were used to collect data for the study. The data collected were analyzed using Means, Standard deviations and Analysis of Variance (ANOVA). The study established that effective leadership roles and practices of Principals and Tutors quality had impact on the academic work of Teacher-trainees. By implication, good leadership practices had a positive relationship with students’ academic work. The results of the ANOVA tests indicated that there was no significant difference in the means of the responses on College Tutor provided by the respondents. The implication is that Tutor quality turn to affect classroom teaching and learning. The respondents from Offinso College had the lowest mean of 2.41on infrastructure, implying that their College infrastructure was the least developed. However, the respondents of Akrokerri had an overall mean of 3.55 which implied that their College infrastructure was moderately developed. The study also revealed that, the higher the academic qualification of College Tutors in their respective area of study, the more likely they are to impact positively on the academic work of Teacher-trainees.